A tangled yarn - Hechtman, Betty, 1947- (Hechtman, Betty, 1947- Yarn retreat mysteries., 2017)
"Casey Feldstein has her hands full with preparations at the Vista Del Mar hotel on the scenic Monterey Peninsula as another yarn retreat begins. The retreaters will be thrown for a loop this time, learning the trendy art of arm knitting and finger crocheting. But not everyone is enthusiastic about trying something new, and Casey is forced to come up with an alternative craft for her less adventurous pupils. Things go from worst to worsted when a travel writer from a neighboring retreat group is found dead in his room among a sea of feathers. When one of the owners of Vista Del Mar pleads for help, Casey gets hooked into the case and must unravel a delicate skein of secrets to catch a killer"--Page 4 of cover.